If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 1 = 27 Reorder the terms: 1 + 6p = 27 Solving 1 + 6p = 27 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6p = 27 + -1 Combine like terms: 1 + -1 = 0 0 + 6p = 27 + -1 6p = 27 + -1 Combine like terms: 27 + -1 = 26 6p = 26 Divide each side by '6'. p = 4.333333333 Simplifying p = 4.333333333
| 7x-6=2x-11 | | z^2=-3 | | 17x/6-4= | | 15.26p+0.11=15.76p+0.14 | | 8x+1=4x+13 | | 5x-9=2x+9 | | -2(4d-3)=-(5d+3) | | 8x+1=3x+1 | | a^2+200=0 | | 3.1x^2-4.2-7.8=0 | | 128-4x=23x+23 | | 5b+1=21 | | 4(4-x)-3=-3x+6 | | 2x+4.4=12.8 | | 15a^5b^12+30a^2b^3-45a^3b^4= | | 5x+9.2=47.7 | | -x+35=2(x+10) | | 6k^2-10k+50=0 | | 4.3x=16.77 | | x+11.5=5.1 | | 2x^2-2x-12= | | 4x+7.3=14.1 | | 4a-7=17 | | 5+(8x-12)4x=-x | | 4x+6.9=28.9 | | (4x+9)(3x+2)= | | 4.1x=15.99 | | x+7.7=5.5 | | 18*x+6=9 | | 5x+7.7=41.2 | | 6h+7=3(4h-71)-8 | | 5x+8x-36=90-5x |